PERAN CUSTOMER SERVICE DALAM MENINGKATKAN PELAYANAN TERHADAP PENUMPANG DI STASIUN BESAR YOGYAKARTA - , RIAN PUTRI N., Fahmi Prihantoro, S.S., S.H., M.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to know the role of customer service Yogyakarta Station to increase service of passengers, to know the assignment of customer service to passengers, and to know the customer service efforts in the face of passenger complaints. This research used observation methods by work practice as customer service in Yogyakarta station, interview methods to customer service official to obtain data, literature methods to obtain data from books, papers, and archives customer service Yogyakarta station. Customer service has a role of giving information and conveying the decision about the complaints of passenger. Servicequality of customer service Yogyakarta station is affected in five service dimensions such as responsiveness, assurance, tangibles, empathy, and reliability. The dimensions will determine passenger satisfaction in the quality of service.